2015
DOI: 10.1007/s10646-015-1569-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in dry grassland communities along a heavy metals gradient

Abstract: The aim of this study was to investigate the variation in plant communities growing on metal-enriched sites created by historical Zn–Pb mining. The study sites were 65 small heaps of waste rock covered by grassland vegetation and scattered mostly over agricultural land of southern Poland. The sites were described in terms of plant coverage, species richness and composition, and the composition of plant traits. They were classified using phytosociological methods and detrended correspondence analysis. Identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…For years, metallophytes of both natural and human-influenced metalliferous soils have focused considerable attention due to their unique appearance and ability to colonize extremely harsh habitats. Through evolution, the plants occurring on metalliferous habitats have developed a range of intriguing adaptive traits, demonstrated as unique morphological, behavioral, and physiological alterations that enable them to avoid or tolerate metal toxicity (Gołębiewski et al 2014 ; Woch et al 2016 ; Wójcik et al 2017 ). Thus, metallophytes possess mechanisms responsible for plant cell protection from excess amount of metallic ions which may get into the protoplast as well as for their detoxification inside the cell by chelation, vacuolar sequestration, or exclusion from the symplast.…”
Section: Introductionmentioning
confidence: 99%
“…For years, metallophytes of both natural and human-influenced metalliferous soils have focused considerable attention due to their unique appearance and ability to colonize extremely harsh habitats. Through evolution, the plants occurring on metalliferous habitats have developed a range of intriguing adaptive traits, demonstrated as unique morphological, behavioral, and physiological alterations that enable them to avoid or tolerate metal toxicity (Gołębiewski et al 2014 ; Woch et al 2016 ; Wójcik et al 2017 ). Thus, metallophytes possess mechanisms responsible for plant cell protection from excess amount of metallic ions which may get into the protoplast as well as for their detoxification inside the cell by chelation, vacuolar sequestration, or exclusion from the symplast.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been focused on this issue in Central Europe, including Poland (Jablonska & Siedlecka 2015; Woch et al 2015), Czech Republic (Pavlů et al 2007;Soudek et al 2015), Hungary (Szabó et al 2015) or Germany (Mayanna et al 2015).…”
mentioning
confidence: 99%
“…Presence or absence of explosives compounds was unable to differentiate treatment groups from one another using standard species diversity metrics (S, H′, D 1 ). Woch et al (2016) [7] found a similar response along a heavy metal gradient and suggested that similarity was due to less tolerant species being removed and more tolerant species coming in and establishing in the newly formed gaps and this trend had also been observed repeatedly in systems under natural disturbance regimes [57]- [61]. This idea is further supported by the significant increase in annual and monocot species presence in RDX plots as well as the increase in annuals CWM in TNT plots.…”
Section: Discussionmentioning
confidence: 53%
“…Increases in annuals and graminoids have been observed in the presence of contaminants [62] [63] [66]. Compositional changes away from zoochorous species has been connected with harsh habitats; particularly young or disturbed ones [7] [82]. Functional richness and divergence have often been linked to community assembly processes [83]- [85] or ecosystem functioning [86]- [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation